The Transformation of Growth Regime and De-industrialization in Japan - Hiroyasu Uemura; Shinji Tahara (Revue de la Régulation)
This study analyzes the long-term transformation of growth regime and the process of de-industrialization in Japan, taking account of domestic institutional changes and international economic relations. Influenced by the structural changes in the manufacturing industry and the long-lasting recession, de-industrialization has accelerated in the Japanese economy since the 1990s. In particular, linkages between the export-goods manufacturing industry and the business-related service industry are analyzed to understand the characteristics of de-industrialization. In this study, we have attempted to extend the theoretical framework of the growth regime in the régulation theory, taking account of long-term industrial structural changes. Both the macroeconomic analysis of growth and distribution and Input-Output Analysis are conducted on the basis of institutional analysis. This study employs the régulationist perspective to consider the possibility of a new growth regime in Japan.